Association of Serum Vitamin D with Serum Cytokine Profile in Patients with Knee Osteoarthritis. (December 2021) - Amini Kadijani, Azade; Bagherifard, Abolfazl; Mohammadi, Fatemeh; Akbari, Abolfazl; Zandrahimi, Farshad; Mirzaei, Alireza
Objective: The role of vitamin D in the pathogenesis of osteoarthritis (OA) is not well understood. In this study, we aimed to investigate the association of serum vitamin D with the serum cytokine profile in patients with primary knee OA. Design: In a cross-sectional study, 116 patients with radiologic diagnosis of grade I to III knee OA were included. The study population included 79 (75.9%) females and 25 (24.1%) males with a mean age of 55.1 ± 9.6 years. The serum concentration of IL-6, IL-8, TNF-α, IL-4, IL-10, IL-13, and vitamin D were assessed using an enzyme-linked immunosorbent assay. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used for the assessment of patient's reported disability associated with knee OA. Results: Serum vitamin D status was deficient, insufficient, and sufficient in 18 (15.5%), 63 (54.3%), 35 (30.2%) patients, respectively. Higher levels of serum IL-6 were observed in patients with vitamin D deficiency ( P = 0.022). The mean serum vitamin D level was not associated with OA grade ( P = 0.88) and WOMAC scores of the patients ( P = 0.67). Serum IL-6 level was significantly associated with both OA grade and WOMAC scores of the patients ( P < 0.001 and P = 0.001, respectively). The vitamin D status was not significantly associated with the serum levels of other evaluated cytokines. Conclusion: Vitamin D deficiency in knee OA seems to be associated with a higher release of IL-6. Therefore, vitamin D supplementation could reduce the disease burden by controlling the IL-6 release.